Engagement of local heroes in managing flood disaster: lessons learnt from the 2014 flood of Kemaman, Terengganu, Malaysia - Othman, Marini; Abdul Latif, Aliza; Maidin, Siti Sarah; Mat Saad, Mohamad Firdaus (InTech Open Science, 2017)
There were many lessons unfolded by the flood disaster which hits the peninsular of Malaysia at year end of 2014. Of particular interest is the success story of good flood management which emerged in Kemaman Terengganu. This chapter sheds some light on the characteristics that has contributed to the success. To enable appreciation of the success, a comparison between selected floods inflicted areas are presented - pointing-out similarity of flood factors which, however, has produced differences in flood impact. Post-disaster study which includes analysis of flood report, site visits (which includes disaster site, flood command centre and relief centres) and interview of personalities involved in the flood incident were conducted. Findings revealed the use of Technology, good Standard Operating Procedure, and engagement of Local Community to be key ingredients to the success. The study recommends that the success of Kemaman to inspire flood management practice for other non-urban flood districts in Malaysia.